2022
DOI: 10.1007/s10551-022-05167-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Work-Related Use of Information and Communication Technologies After Hours on Time Theft

Abstract: Time theft is a prevalent, costly, and generally discreet employee activity in firms; nonetheless, very limited research is available on it. To explore why, how, and when employees exhibit time theft, we investigate the influence mechanism of work-related use of information and communication technologies after hours (W_ICTs) on time theft from the perspective of resource gain and loss. Our study found that W_ICTs significantly promotes employee time theft. Emotional exhaustion and moral disengagement play a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Bowling and Gruys ( 2010 ) noted that workplace deviance is a situation-specific construct and its measure should include key behaviors that are important to a specific job or organization. More recently, researchers have begun to focus on several sub-dimensions of workplace deviance, beyond those that have typically been examined in the literature, such as job neglect, time theft, and sabotage (e.g., Hu et al, 2022 ; McLarty et al, 2021 ; Xu et al, 2022 ). In our opinion, job neglect might be most relevant for service organizations, such as hospitals, as this particular type of dysfunctional behavior can have detrimental effects on service quality and customer satisfaction, ultimately leading to poor organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowling and Gruys ( 2010 ) noted that workplace deviance is a situation-specific construct and its measure should include key behaviors that are important to a specific job or organization. More recently, researchers have begun to focus on several sub-dimensions of workplace deviance, beyond those that have typically been examined in the literature, such as job neglect, time theft, and sabotage (e.g., Hu et al, 2022 ; McLarty et al, 2021 ; Xu et al, 2022 ). In our opinion, job neglect might be most relevant for service organizations, such as hospitals, as this particular type of dysfunctional behavior can have detrimental effects on service quality and customer satisfaction, ultimately leading to poor organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, previous studies investigating the reciprocal relationship between abusive supervision and workplace deviance have used broader conceptualizations of workplace deviance construct (e.g., Lian et al, 2014a ; Simon et al, 2015 ); consequently, numerous potential sub-dimensions of workplace deviance have been ignored in the abusive supervision literature (Bowling & Gruys, 2010 ; Mackey, 2021 ). Recent research on deviant workplace behavior has demonstrated that various types of workplace deviance, such as job neglect, time theft, and sabotage, are differentially and uniquely related to potential antecedents and outcomes (e.g., Hu et al, 2022 ; McLarty et al, 2021 ; Xu et al, 2022 ). In this study, we focus exclusively on job neglect and posit that abusive supervision and job neglect are reciprocally related.…”
Section: Introductionmentioning
confidence: 99%
“…Although we strictly followed the translation and translation back procedures to decrease errors and the scale showed good reliability and validity, there could still be some limitations when applied to Chinese situations directly. In future, we will develop localized scales to improve the applicability ( Brown and Ryan, 2003 ; Yao et al, 2020a , 2021 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, as the top managers of these enterprises have a good cooperative relationship with the members of the research group, this research has gained their strong support; on the other hand, these technology enterprises are in urgent need of rapid improvement of innovation ability, so they focus more on the knowledge hiding of employees. These practices are common in academic research, e.g., Zhao et al (2016) , Yao et al (2021) , Xu et al (2022) , etc. The research group promised the companies to share the research results and provide free consulting services.…”
Section: Methodsmentioning
confidence: 99%
“…Research on the impact of W_ICTs has not yet reached a consensus. Some studies indicate that W_ICTs can intensify employee workloads during non-work hours, which may lead to several negative outcomes such as marital fatigue, work-family conflicts, time theft, deviant behavior, emotional exhaustion, and reduced job satisfaction [ [7] , [8] , [9] , [10] , [11] , [12] ]. Conversely, other scholars argue that W_ICTs can have positive effects on employees by improving workplace effectiveness, engagement, focus on opportunities, work-to-family enrichment, and interpersonal interaction [ [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%